Students’ Error Analysis in solving Contextual Problem of Flat-Sided Geometry Based on Nolting’s Theory Depends on Gender - Anissa Teguh Saputri; Edy Suprapto; Swasti Maharani (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
When students solve math problems with flat-sided geometry, there are still many errors made by students. This is because mathematics has mathematical concepts and principles that students do not understand well, so that it can cause errors in solving mathematical problems of flat-sided geometry. The purpose of this study is to analyze the types of student errors in solving the problem of flat-sided geometry depends on Nolting's Theory. This research uses a qualitative approach. The instrument used is a flat-sided geometry test and interview guidelines. The results of this study can be used as an effort to improve students' ability in solving contextual problems in the material of building a flat side space. Based on the results of the study, information was obtained that there were 5 types of errors, namely reading instructions errors, carelessness errors, conceptual errors, application errors, students' test errors in solving contextual problems based on Nolting's theory. Male student subjects in solving contextual problems of flat-sided wake-up material made a lot of reading errors, carelessness errors, conceptual errors, and test-taking errors. Female student subjects in solving contextual problems with flat-sided geometry make a lot of errors, including carelessness, application errors, and test-taking errors.